Investigating Teachers' Perceptions of Educational Technology Philosophy in ELE Through the Flipped Classroom Model - S, Kartika (Lentera: Jurnal Ilmiah Kependidikan, 2024)
The purpose of this study is to find out how instructors believe about adopting the Flipped Classroom approach from a techno-pedagogical philosophy when teaching English. Furthermore, this study collects data from teachers on their perceptions of the Flipped Classroom model in the English course through surveys and interviews. EFL teachers who have adopted the Flipped Classroom model provide data. This current study employed a semi-structured interview and a five-point Likert scale questionnaire as the research instrument. A mixed-method research was the research design in this study. Twenty English instructors were chosen on purpose. After collecting the data, the researcher analyzed the data using descriptive and statistical analysis. The results show that EFL teachers' opinions of the flipped classroom concept are usually positive. This study highlights the beneficial effects on students' learning, acknowledges implementation difficulties, and emphasizes how important it is to include teachers' viewpoints to develop effective teaching strategies. The popularity and possible advantages of the Flipped Classroom model in English courses are also greatly influenced by the opinions of English teachers.